Dylematy pomiaru kapitału intelektualnego w systemie zarządzania jakością według PN-EN ISO 9001:2001 - Szczepańska, Katarzyna (Intellectual Capital Measurement Aspects in Quality Management System PN-EN ISO 9001:2001, 2008)
The paper presents chosen aspects of Value Based Management in the context for a discussion of the relationship between intellectual capital and requirements of quality standard PN-EN ISO 9001:2001 and management principles as well. The presentation defines the intellectual capital with reference to different subject areas and discusses its structure. The review of the methods of measuring the intellectual capital shows their implications for decision making by managers. The article concludes with a discussion regarding possibilities of including and measuring the intellectual capital in normative solutions. The author reaches the conclusions that ISO requirements are only possible connected with the structure of the intellectual capital, so the main question is the way of implementing idea of Value Based Management to PN-EN ISO 9001:2001. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 279-291